Standardization of hypo-osmotic solutions to study the functional integrity of post thaw bull spermatozoa - SINGH, AJEET; SINGH, JAGIR; MATHAROO, J S; SINGH, PRAHLAD (The Indian Journal of Animal Reproduction, 2023)
Functional integrity of sperm plasma membrane was studied in post thaw bull semen using Hypo-osmotic swelling test(HOST). Frozen semen after thawing was subjected to hypo-osmotic swel!ing test (HOST) in hypo-osmotic solutions of osmolarity75, 100 and 150 mOsmol/L. The overall average tail curling with 75, 100 and 150 mOsmol/L were recorded 17.55±8.28, 46.46±11.97and 34.27±7.97%, respectively. Maximum tail curling was observed with JOO mOsmol/L solution which was significantly (P < 0.05)higher than the 75 ahd 150 mOsmol/L solutio.
Keywords: HOST; functional integrity; post thaw semen; curled tail spermatozoa; bull